Highly porous Pd nanostructures and reduced graphene hybrids: excellent electrocatalytic activity towards hydrogen peroxide. (8th December 2015) - Sahu, Subash Chandra; Behera, Tapan Kumar; Dash, Ajit; Jena, Bijayalaxmi; Ghosh, Arnab; Jena, Bikash Kumar
Abstract : A new approach has been developed for highly porous Pd nanostructure–graphene hybrids as efficient electrocatalysts towards reduction of H2 O2 . Abstract : A facile approach has been developed for the synthesis of highly porous Pd nanostructures (PPd NSs) and their graphene hybrid (RG-PPd NSs). The PPd NSs are well-dispersed on the graphene support and retain their unique morphology. The RG-PPd NS modified electrode shows high sensitivity towards H2 O2 without the usage of a redox mediator/enzyme.